Effects of pulsed laser surface treatments on microstructural characteristics and hardness of CrCoNi medium-entropy alloy. Issue 24 (17th December 2019) - Chai, Linjiang; Xiang, Kang; Xia, Jiying; Fallah, Vahid; Murty, Korukonda L.; Yao, Zhongwen; Gan, Bin
ABSTRACT: A hot-swaged/annealed CrCoNi medium-entropy alloy (MEA) was surface-treated by pulsed laser at two different powers (400 and 200 W). Microstructural characteristics of the laser-modified zones were characterised and analysed by energy dispersive spectroscopy, electron backscatter diffraction and electron channelling contrast imaging techniques. Results show that melting and rapid solidification occur on the surfaces of both laser-treated specimens, and profuse annealing twins existing in the initial microstructures are essentially eliminated in the melting zone (MZ) with plentiful low-angle boundaries appearing. Meanwhile, the initial equiaxed grains are replaced by new grains in the MZ with either granular or columnar appearance (in the 2D cross-sectional views). These grains are comprised of fine cellular structures with relatively uniform sizes (∼1–2 μm in width/diameter), the formation of which is related to the segregation of Cr during solidification. With the laser power decreasing from 400 to 200 W, the volume of the MZ and grain sizes in its interior are reduced. This is due to less heat supply and faster cooling caused by reducing the laser power. Hardness tests reveal that the surfaces of both the laser-treated specimens are slightly softened (by 10–20%), and quantitative analyses suggest that this is mainly related to grain coarsening and the disappearance of annealing twins in the MZ.